Estudio de factibilidad para la implementación de una hostería ecológica con servicios de calidad, en Quevedo, Provincia de Los Ríos, año 2020 - Yánez Tigrero, Jorge Gabriel (2020)
This project aimed to carry out a feasibility study for the implementation of an ecological hostel with quality services in Quevedo. Employing a micro evaluation, the current state of tourism was identified and the current situation of the operation of tourist establishments was analysed, where fallacies were detected in the services offered to tourists. A problem that Quevedo still has is that despite having excellent commercial activity and the financing of businessmen who have decided to invest in the city because of its economic development, it lacks a tourist promotion and publicity that would enhance this sector. The implementation of an ecological hostel with quality services will influence the economic and social development of the canton since, with its environmentally friendly infrastructure many tourists will choose this site as an option for vacationing and so they will also be able to know a little more of Quevedo. Likewise, excellent service should be provided to people so that they can feel satisfied and decide to return to the city.